2021
DOI: 10.3389/fimmu.2020.621441
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Signature Induced by SARS-CoV-2 Spike Protein in a Mouse Model

Abstract: Although COVID-19 has become a major challenge to global health, there are currently no efficacious agents for effective treatment. Cytokine storm syndrome (CSS) can lead to acute respiratory distress syndrome (ARDS), which contributes to most COVID-19 mortalities. Research points to interleukin 6 (IL-6) as a crucial signature of the cytokine storm, and the clinical use of the IL-6 inhibitor tocilizumab shows potential for treatment of COVID-19 patient. In this study, we challenged wild-type and adenovirus-5/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 45 publications
1
62
1
Order By: Relevance
“…The rationale of our findings supporting the repurposing of JAK inhibitors to improve the treatment strategies for COVID-19 could be explained by the following mechanisms. Much evidence has shown that severe COVID-19 patients might present with an exaggerated immune response, characterized by increased interleukin (IL)-6, IL-2, IL-7, IL-10, granulocyte-colony stimulating factor (G-CSF), interferon-γ (IFNγ), macrophage inflammatory protein 1α (MIP1A), and tumor necrosis factor-α (TNF-α) [26] , [27] , [28] , [29] . In contrast, JAK inhibitors targeting JAK1, JAK2, JAK3, and tyrosine kinase-2 (TYK2) can downregulate these cytokines to further decrease inflammatory responses [27] , [28] , [30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale of our findings supporting the repurposing of JAK inhibitors to improve the treatment strategies for COVID-19 could be explained by the following mechanisms. Much evidence has shown that severe COVID-19 patients might present with an exaggerated immune response, characterized by increased interleukin (IL)-6, IL-2, IL-7, IL-10, granulocyte-colony stimulating factor (G-CSF), interferon-γ (IFNγ), macrophage inflammatory protein 1α (MIP1A), and tumor necrosis factor-α (TNF-α) [26] , [27] , [28] , [29] . In contrast, JAK inhibitors targeting JAK1, JAK2, JAK3, and tyrosine kinase-2 (TYK2) can downregulate these cytokines to further decrease inflammatory responses [27] , [28] , [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence has shown that severe COVID-19 patients might present with an exaggerated immune response, characterized by increased interleukin (IL)-6, IL-2, IL-7, IL-10, granulocyte-colony stimulating factor (G-CSF), interferon-γ (IFNγ), macrophage inflammatory protein 1α (MIP1A), and tumor necrosis factor-α (TNF-α) [26] , [27] , [28] , [29] . In contrast, JAK inhibitors targeting JAK1, JAK2, JAK3, and tyrosine kinase-2 (TYK2) can downregulate these cytokines to further decrease inflammatory responses [27] , [28] , [30] . In addition, baricitinib (a JAK1/2 inhibitor) may affect the cellular viral entry of SARS-CoV-2 through potential inhibitory effects on AP2-associated protein kinase 1 and cyclin G-associated kinase [31] , [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Additional limitations may arise from the selection of Poly(I:C) to mimic viral infection as opposed to a cell-based infection system when evaluating compounds as potential treatments for SARS-CoV-2 infections. However, extensive reports have provided sound evidence for the use of this model, showcasing how it imitates in vivo responses of the human lung to viral infection, and how it is currently used to assess expression alterations of host cell receptors associated with SARS-CoV-2 [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…To follow up on the RNA-Seq data, future detailed analyses of selected differently expressed genes and proteins of interest may be conducted by real-time RT-qPCR, Western blotting and other in vitro techniques, and by harnessing gene-knockout and other animal models to further investigate their specific functions in vivo during SARS-CoV-2 infection. Mice expressing human ACE2 and challenged with recombinant SARS-CoV-2 spike protein can elucidate the latter's contribution to COVID-19 pathology [74]. Another strategy for transcriptomic and other analyses is to infect cells expressing human ACE2 receptor with lentiviral particles expressing SARS-CoV-2 proteins, e.g., spike glycoprotein [75].…”
Section: Discussionmentioning
confidence: 99%